Analisis Faktor - Faktor yang Berhubungan dengan Kehamilan pada Remaja Putri di Wilayah Kerja Puskesmas Cerme Kabupaten Gresik Tahun 2025 - Nur Arini Al Fisyah; Budi Prasetyo; Wahyul Anis (Lembaga Pengembangan Kinerja Dosen, 2026)
Cerme District in Gresik Regency has one of the highest rates of adolescent pregnancy, with 187 cases recorded in 2023 and 118 cases in 2024, according to the Gresik Regency Health Office (2025). This indicates that adolescent pregnancy remains a critical issue. Factors contributing to this issue include low reproductive health knowledge, insufficient parental involvement in sexuality education, and negative peer influence. This study used a quantitative approach with a cross-sectional design, focusing on adolescent girls aged 11-20 years in the Cerme Public Health Center area. A sample of 98 respondents was selected through random sampling. Data was collected using structured questionnaires and analyzed using univariate and bivariate analyses with the Chi-Square test (p < 0.05). Results showed that most respondents were aged 14-16 years, with menarche occurring between 11-15 years, and their parents' education level was mainly senior high school. Most adolescents had good knowledge of pregnancy (96.9%), with 53% reporting good parental involvement, and 49% reported poor peer influence. The Fisher Exact Test indicated no significant relationship between knowledge and adolescent pregnancy (p = 0.228), but a significant relationship was found between parental role (p = 0.023) and peer influence (p = 0.006) with adolescent pregnancy. In conclusion, strengthening reproductive health education and improving communication between parents and children are essential to preventing adolescent pregnancy.